HAEMAGGLUTINATION ACTIVITY OF THE EXTRACTS FROM SOME VIETNAM MARINE INVERTEBRATES - Trung, Dinh Thanh; Dieu Trang, Vo Thi; Duy Ngoc, Ngo Thi; Hoai Trinh, Phan Thi; Hai Yen, Tran Thi; Hung, Le Dinh (Vietnam Journal of Biotechnology, 2018)
Aqueous extracts from 21 species of Vietnam marine invertebrates, including 11 bivalve and 10 gastropod species, were examined for haemagglutination activity using native and enzyme-treated different animal and human erythrocytes. The 8 bivalve and 10 gastropod species were found to have haemagglutinination activities toward at least one type of erythrocyte tested. A total of 86% of marine invertebrate species surveyed were active. Strong activity was detected in extracts from two bivalve species (Tridacna squamosa and Geloina coaxans) and three gastropod species (Tutufa rubeta, Pleuroploca trapezium and Tectus conus) with enzyme-treated rabbit, horse and human A, B, O erythrocytes. In a haemagglutination–inhibition test with various monosaccharides and glycoproteins, haemagglutination activities of two extracts from T. rubeta and P. trapezium had no affinity for any of the monosaccharides and glycoproteins tested, while activities of the extracts from T. squamosa and T. conus were strongly inhibited by porcine stomach mucin tested, suggesting the presence of lectins specific for O-glycans of these species. The activities of four marine invertebrate extracts were stable over a wide range ofpH and temperature. The haemagglutination activities of T. rubeta and P. trapezium extracts were independent of the presence of divalent cations, whereas the haemagglutination activity of extracts from T. squamosa and T. conus were slightly dependent on the presence of divalent cations. The results suggest that Vietnam marine invertebrates may be good sources of useful lectins for biochemical and biomedical applications.